Handbook of clay science - Bergaya, Faiza; Theng, B. K. G.; Lagaly, Gerhard (Developments in clay science, 2006)
The first general texts on clay mineralogy and the practical applications of clay, written by R.E. Grim, were published some 40-50 years ago. Since then, a vast literature has accumulated but this information is scattered and not always accessible. The Handbook of Clay Science aims at assembling the scattered literature on the varied and diverse aspects that make up the discipline of clay science. The topics covered range from the fundamental structures (including textures) and properties of clays and clay minerals, through their environmental, health and industrial applications, to their analysis and characterization by modern instrumental techniques. Also included are the clay-microbe interaction, layered double hydroxides, zeolites, cement hydrates, genesis of clay minerals as well as the history and teaching of clay science. No modern book in the English language is available that is as comprehensive and wide-ranging in coverage as the Handbook of Clay Science. In providing a critical and up-to-date assessment of the accumulated information, this will serve as the first point of entry into the literature for both newcomers and graduate students, while for research scientists, university teachers, industrial chemists, and environmental engineers the book will become a standard reference text. * Presents contributions from 66 authors from 18 different countries who have come together to produce the most comprehensive modern handbook on clay science * Provides up-to-date concepts, properties, and reactivity of clays and clay minerals in a one-stop source of information * Covers classical and new environmental, industrial, and health applications of clays, as well as the instrumental techniques for clay mineral analysis * Combines geology, mineralogy, crystallography with physics, geotechnology, and soil mechanics together with inorganic, organic, physical, and colloid chemistry for a truly multidisciplinary approach.